Reforming the Coroner: Death Investigation Manuals in Ontario 1863 - 1894 - Leslie, Myles (Ontario History)

(untitled) (The Ontario Historical Society, 2008)
This article traces the evolution of coroners’ manuals as published in nineteenth-century Canada West and Ontario. Rather than study the individual men who investigated suspicious deaths and then held inquests, it examines the coroner as an imagined and ideal type. The first three editions of A Practical Treatise on the office and duties of Coroners, embody not just formal rules and practical advice on doing the job, but the hopes and aspirations of their acknowledged author, William Fuller Alves Boys, and his ghostwriter the respected jurist James Robert Gowan. The article examines trends and changes in the three editions of the manual as both Boys’ career and the government in Ontario develop. Boys’ story, reflected in the evolving manuals, is that of an emerging class of experts and professionals involved in the administration of government and justice in Ontario.